Analysis of Teaching Learning and Assessment in Private Schools within Independent Curriculum Framework - sumantri, kun; Koesoemo Ratih; Muamaroh (Samudra Publisher, 2026)
This research was conducted by analyzing the schedule of teaching and learning activities in private Islamic boarding schools in Pekalongan at the level Junior High School and the implementation of assessments in junior high schools in accordance with the implementation of the Merdeka Curriculum standards. Specifically, the subjects taught to students, how much time is allocated for each subject, and what assessments are conducted in schools. Is the implementation in line with what has been outlined in the Merdeka Curriculum. Data was collected through a literature review from the Ministry of Education's website to find a reference for the Merdeka Curriculum implementation standards and to identify data findings in the field obtained through field observations. The data was analyzed using qualitative descriptive methods to then draw conclusions. The results of this study the number of subjects in private Islamic boarding schools is more than the number of subjects specified in the independent curriculum which is 11 subject. In detail there are 22 subjects at grade 7and grades 8 and 9 have 23 subjects. The number of lesson hours per week at private Islamic boarding schools is more than the number of lesson hours determined by the independent curriculum. In detail, in grades 7 and 8, the total number of teaching hours in one week is 52 hours, while in grade 9, the total number of teaching hours is 53 hours. This data shows that the implementation curriculum private Islamic boarding schools is not in line with Merdeka curriculum.